(3aQjOI efjSI aj MGd ONhd GdJQc HdO bSfWjfIs ((3GdYfJQj Hf eMeO s)
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdCMO hdeG cGfJ GdCNHGQ GdTGFYI jMJGL (B[(3cPG(B] (3cd GddHjH GdMGPb EdjgG EbJVi GdMGd dPdc JQLeI dWjaI aCdReJ faSi dbQY gPG GdHGH hSejJgG aQjOI efSjI ai MGd ONhd GdJQc HdO bSfWjfI s
(3BNQgG (B:s
(3GfJgi gPG GdJGQjN GdeMJhi Ydi cd MGOK ZQjH XQja hfRd McGe GdOhdI GdaQGfUhjI HSQYjJge heedcJge hGdHbGA ddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B193s
(3gcPG hQO GdYfhGf Ydi GdfSNIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B310 s
Keywords: (3GdJGQjNs